Pelatihan Bahasa Inggris untuk Guru dan Staff SMP Darul Ulum 1 Peterongan Jombang - Wim Banu Ukhrowi (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Proficiency in English is vital for participation in the global knowledge economy, providing access to information, education, and technological advancements. Recognizing this, SMP Darul Ulum 1 Peterongan Jombang collaborated with Unipdu Jombang to organize an English training program for its teachers and staff. This program aimed to enhance participants' English competency to deliver effective instruction and foster a conducive learning environment. The month-long program employed interactive methodologies covering grammar, vocabulary, phonetics, teaching methodology, and technology integration. Results show significant improvement in participants' English skills, with implications for teaching effectiveness and student outcomes. The success of this program elevates the school's reputation and competitiveness in providing quality education. Ongoing professional development and a supportive English environment are recommended for sustained improvement.